2020
DOI: 10.1182/bloodadvances.2019001275
|View full text |Cite
|
Sign up to set email alerts
|

Metaphase cytogenetics and plasma cell proliferation index for risk stratification in newly diagnosed multiple myeloma

Abstract: Metaphase cytogenetic abnormalities, plasma cell proliferation index (PCPro), and gain 1q by fluorescence in situ hybridization (FISH) are associated with inferior survival in newly diagnosed multiple myeloma (MM) treated with novel agents; however, their role in risk stratification is unclear in the era of the revised International Staging System (R-ISS). The objective of this study was to determine if these predictors improve risk stratification in newly diagnosed MM when accounting for R-ISS and age. We stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 37 publications
0
11
2
Order By: Relevance
“…Similarly in a recent study on 292 newly diagnosed MM patients by Barilà et al, 2020, concomitant trisomies 9/11/15 were the most powerful prognostic factor ( P < 0.01), followed by IGH rearrangement ( P < 0.04), although in the opposite direction [ 20 ]. Also Mellors et al in 2020 revealed that R-ISS stage and age 70 years were associated with inferior OS in the base model [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly in a recent study on 292 newly diagnosed MM patients by Barilà et al, 2020, concomitant trisomies 9/11/15 were the most powerful prognostic factor ( P < 0.01), followed by IGH rearrangement ( P < 0.04), although in the opposite direction [ 20 ]. Also Mellors et al in 2020 revealed that R-ISS stage and age 70 years were associated with inferior OS in the base model [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies used metaphase cytogenetics and discovered that in many multiple myeloma cases, it was not possible to obtain metaphase spreads for examination. The ability, therefore, to generate abnormal metaphase spreads per se is considered a poor prognostic factor ( 22 ). The presence of a complex karyotype and detection of monosomy 13 on metaphase analysis are also poor prognostic factors; however, many characteristic myeloma markers initially identified by Southern blot are karyotypically silent [e.g., t(4;14)], leading to CD138-selected interphase FISH (iFISH) being the preferred test.…”
Section: Features Of High-risk Diseasementioning
confidence: 99%
“… * Large FLs (diameter >2.5 cm) associated with site-specific enrichment of HiR driver mutations consistent with them being key mediators of drug resistance and treatment failure [ 86 100 ]. ** Certain EME sites seemed to carry worse prognosis with 3-year PFS differing according to involved organs: kidney (59.5%), skin (20.1%), lymph nodes (37.6%), CNS (47.9%), lung/respiratory tract (44.4%), GI/liver (22.5%), and spleen, ovaries, and testes (60.0%).…”
Section: Beyond the R-iss: High-risk Clinical Featuresmentioning
confidence: 99%